Simulation of ozone loss in the Arctic winter 2004/05 - Grooß, J.-U.; Müller, R. (Geophysical Research Letters, 2007)
We present simulations of stratospheric ozone depletion in the Arctic winter 2004/2005 by the Chemical Lagrangian Model of the Stratosphere (CLaMS). This winter is among the coldest on record with large observed ozone losses. It is also different from previously analyzed winters, as ozone mixing ratios within the polar vortex were not homogeneously distributed. The reason for the untypical ozone distribution is a second transport barrier that existed at the time of vortex formation. The simulations agree well with ozone measurements by the Fourier Transform Spectrometer (ACE-FTS). The simulated vortex average column ozone loss between 380 and 550 K potential temperature (+/- 1 sigma) was 69 +/- 21 Dobson Units on 23 March. The simulated ozone loss is in approximate agreement with some published estimates, but is significantly lower than others. A possible reason for this difference is the inhomogeneous ozone distribution within the vortex which makes it more complicated to estimate of ozone loss.